Influence of Donor‐Substituents on Triphenylamine Chromophores Bearing Pyridine Fragments. Issue 9 (20th February 2019) - Tydlitát, Jiří; Fecková, Michaela; le Poul, Pascal; Pytela, Oldřich; Klikar, Milan; Rodríguez‐López, Julián; Robin‐le Guen, Françoise; Achelle, Sylvain
Abstract : Efficient synthetic routes that combine different palladium‐catalyzed cross‐coupling reactions have been developed for the preparation of a new family of push‐pull derivatives in which pyridine was used as the acceptor group and different para ‐substituted diphenylamines as the donor groups. All compounds showed absorption in the UV/Vis region and blue‐green emission with high quantum yields. Significant red shifts were observed in the absorption and fluorescence emission maxima on increasing the electron‐donating ability of the substituents or on incorporating a π‐conjugated linker. This finding can be explained on the basis of enhanced intramolecular charge transfer (ICT). Strong emission solvatochromism confirmed the formation of an intramolecular charge‐separated emitting state. The HOMO‐LUMO energy gaps have been estimated by experimental electrochemical measurements and the results were interpreted with the aid of DFT calculations. The thermal behavior of all materials has also been studied by differential scanning calorimetry. Abstract : A series of push‐pull chromophores with a pyridine electron‐withdrawing fragment and methoxy‐, 9 H ‐carbazol‐9‐yl‐, and 5‐methoxythiophen‐2‐yl‐substituted diphenylamino groups as electron‐donating units was designed.